Teknik Chunking Dipadu Writing is Thinking untuk Mengendalikan Extraneous Cognitive Load Siswa - Meirin Dwiningtyas Putri; Adi Rahmat; Yayan Sanjaya (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2022)
Extraneous cognitive load (ECL) is a related to the design or learning strategies in learning activities. This study aims to control students’ extraneous cognitive load by using chunking technique with writing is thinking in the human reproductive system learning. This research was conducted at one of the Senior High School in Tasikmalaya City for the 2020/2021 academic year. The research method used quasi-experimental with posttest only control group design. The research subjects were 56 samples divided into two groups, namely the experimental group (28 students) and the control group (28 students). The instrument used in this research is a subjective rating scale questionnaire with a scale of 1 to 8 including indicators of the student responses about the learning strategies used and student responses to the given task. The results showed that the students’ extraneous cognitive load of the experimental group was lower than the control group. Based on the result of statistic analysis using SPSS version 23 software, the students’ extraneous cognitive load between the experimental group and the control group was significantly different